MEN AND THEIR PORTRAYAL IN BELOVED: THE FRAMING OF BLACK AND WHITE MASCULINITIES IN A SLAVE-OWNING WORLD - Dzregah, Augustina E (European Scientific Journal, ESJ, 2013)
Because Toni Morrison explores the lives of women in all her novels, most critics read her works as mainly woman-centered while most studies of her male characters present the men and their stories as secondary to that of the women characters. However, Morrison also explores the constructions of masculinities as complicated by race and history in her works. Through her male characters’ lives in Beloved, Morrison demonstrates the complexities and paradoxes inherent in the making of black masculinities and the oppression and denial of selfhood they experience in a slaveowning era. She thus tells the stories of black male characters and invests them with voice and visibility. To clearly bring out the realities of being black, male and subordinated, she contrasts black masculinities with the dominant white hegemonic masculinity practices that restrict and negatively define black men. Using the lives of selected black and white male characters in Beloved, this paper examines the manifestations of white hegemonic masculinities in the white characters’ lives and their impact on black men. It also analyzes the creation and operations of black or subordinated masculinities within the oppressive and often horrific circumstances in which black men find themselves.